Snake venomics of Bothrops punctatus, a semiarboreal pitviper species from Antioquia, Colombia (2014)
ABSTRACT: Bothrops punctatus is an endangered, semi-arboreal pitviper species distributed in Panama, Colombia, and Ecuador, whose venom is poorly characterized. In the ́ present work, the protein composition of this venom was profiled using the ‘snake venomics’ analytical strategy. Decomplexation of the crude venom by RP-HPLC and SDS-PAGE, followed by tandem mass spectrometry of tryptic digests, showed that it consists of proteins assigned to at least nine snake toxin families. Metalloproteinases are predominant in this secretion (41.5% of the total proteins), followed by C-type lectin/lectin-like proteins (16.7%), bradykinin-potentiating peptides (10.7%), phospholipases A2 (9.3%), serine proteinases (5.4%), disintegrins (3.8%), L-amino acid oxidases (3.1%), vascular endothelial growth factors (1.7%), and cysteine-rich secretory proteins (1.2%). Altogether, 6.6% of the proteins were not identified. In vitro, the venom exhibited proteolytic, phospholipase A2, and L-amino acid oxidase activities, as well as angiotensin-converting enzyme (ACE)-inhibitory activity, in agreement with the obtained proteomic profile. Cytotoxic activity on murine C2C12 myoblasts was negative, suggesting that the majority of venom phospholipases A2 likely belong to the acidic type, which often lack major toxic effects. The protein composition of B. punctatus venom shows a good correlation with toxic activities here and previously reported, and adds further data in support of the wide diversity of strategies that have evolved in snake venoms to subdue prey, as increasingly being revealed by proteomic analyses.